Indigenising Education: Scales, Interfaces and Acts of Citizenship in Sápmi - Sollid, Hilde; Olsen, Torjer Andreas (Junctures: The Journal for Thematic Dialogue (No. 20, 2019, "Indigenisation"), 2019)
As Indigenous people reclaim their position after centuries of oppression, the tensions between Indigenous needs and national demands surface. This is also the case of the Indigenous Sámi in Norway. After a long period of colonisation, recognition of the indigenous Sámi people and their language and culture is replacing the politics of erasure. In this process, the educational system is the institution where this new direction can reach the farthest. Rather than seeing Indigenous education as static endpoint in opposition towards mainstream education, we theorise that indigenising education is better understood as a process and as a continuum where citizens with different subject positions engage and interact in a cultural interface. The theorising is based on a case study from Gáivuotna-Kåfjord-Kaivuono on the Norwegian side of Sápmi.